(untitled) (World Bulletin of Physical Education and Sports Science, 2025)
The article explores the theoretical and practical foundations of integrating ecological, ethical, and healthy lifestyle values into the teaching of sports games. Sports lessons are analyzed as an effective means not only for improving physical fitness but also for fostering social responsibility, environmental awareness, and moral qualities among students. The research examines pedagogical technologies aimed at promoting a conscious attitude toward a healthy lifestyle, instilling environmental protection values, and strengthening moral principles through sports activities.